Metallicity Dependence of Giant Planets around M Dwarfs - Tianjun Gan; Christopher A. Theissen; Sharon X. Wang; Adam J. Burgasser; Shude Mao (The Astrophysical Journal Supplement Series)
We investigate the stellar metallicity ([Fe/H] and [M/H]) dependence of giant planets around M dwarfs by comparing the metallicity distribution of 746 field M dwarfs without known giant planets with a sample of 22 M dwarfs hosting confirmed giant planets. All metallicity measurements are homogeneously obtained through the same methodology based on the near-infrared spectra collected with a single instrument SpeX mounted on the NASA Infrared Telescope Facility. We find that (1) giant planets favor metal-rich M dwarfs at a 4 σ –5 σ confidence level, depending on the band of spectra used to derive metallicity; (2) hot ( a / R _* ≤20) and warm ( a / R _*  > 20) Jupiters do not show a significant difference in the metallicity distribution. Our results suggest that giant planets around M and FGK stars, which are already known to prefer metal-rich hosts, probably have a similar formation channel. In particular, hot and warm Jupiters around M dwarfs may have the same origin as they have indistinguishable metallicity distributions. With the refined stellar and planetary parameters, we examine the stellar metallicities and the masses of giant planets where we find no significant correlation. M dwarfs with multiple giant planets or with a single giant planet have similar stellar metallicities. Mid-to-late type M stars hosting gas giants do not show an apparent preference to higher metallicities compared with those early M dwarfs with gas giants and field M dwarfs.